Effects of a hemostatic powder hemospray on coagulation and clot formation - Holster, I. Lisanne; van Beusekom, Heleen M. M.; Kuipers, Ernst J.; Leebeek, Frank W. G.; de Maat, Moniek P. M.; Tjwa, Eric T. T. L. (Endoscopy, 2015)
Background and study aims: Hemospray (Cook Medical Inc., Winston-Salem, North Carolina, USA) is a novel, hemostatic, powder spray that has been developed for gastrointestinal use. The powder is thought to achieve hemostasis by concentrating clotting factors and forming a mechanical plug on the injured blood vessel. However, no detailed studies on the hemostatic mode of action have been performed. The aim of this study was to examine the effects of Hemospray on coagulation and clot formation both in vitro and in vivo. Materials and methods: Recalcification time, thromboelastometry using EXTEM and INTEM assays, and plasma coagulation tests (activated partial thromboplastin time and prothrombin time) were carried out on blood samples mixed with Hemospray, and compared with talcum powder (negative control) and kaolin (positive control) at 1 mg/mL and 10 mg/mL. Scanning electron microscopy (SEM) and light microscopy were performed on in vitro thrombi and on gastric thrombi from an animal model of gastrointestinal hemorrhage treated with Hemospray. Results: The median recalcification time of whole blood was 187.5 seconds. The addition of 1 mg/mL and 10 mg/mL Hemospray significantly shortened this time (median 60 and 45 seconds, respectively; P < 0.05). The median clotting time of whole blood, measured using the INTEM assay, was 160 seconds (interquartile range [IQR] 159 – 176.5) and this was also significantly reduced by the addition of Hemospray (91 seconds [IQR 84 – 102]; P = 0.005). The plasma prothrombin time of 11.6 seconds was significantly reduced by Hemospray (9.5 seconds; P = 0.011). SEM of in vivo clots demonstrated that Hemospray rapidly interacted with whole blood, forming one confluent mass over the bleeding site. In sufficient amounts, Hemospray was able to deform and pack erythrocytes. Conclusions: Hemospray covered the bleeding site and enhanced clot formation in vivo, and shortened coagulation time in vitro. Elaboration of these unique properties in clinical practice will help to optimize future endoscopic hemostasis with Hemospray.